2013
DOI: 10.1007/s12094-013-1016-2
|View full text |Cite
|
Sign up to set email alerts
|

Early volumetric change and treatment outcome of metastatic brain tumors after external beam radiotherapy: differential radiotherapy for brain metastasis

Abstract: Low-dose WBRT with selective boost was feasible and effective. Our results pose the rationale of future trial of differential radiation therapy (RT), which prescribes different radiation dose according to the tumor density in metastatic brain tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…In contrast with the studies reported in Fig. 7 , other studies did not find an association with LC for age [ 175 180 , 185 ], gender [ 174 176 , 178 180 ], extracerebral metastases [ 174 , 177 , 179 , 180 , 185 ], extracranial metastasis [ 178 ], number of metastases [ 177 , 178 , 185 ], the interval from first diagnosis to WBRT [ 174 , 177 , 179 ], KPS [ 178 , 185 ], primary tumor type [ 177 , 179 ] and RPA class [ 185 ] for treatment with WBRT alone.…”
Section: Resultscontrasting
confidence: 72%
“…In contrast with the studies reported in Fig. 7 , other studies did not find an association with LC for age [ 175 180 , 185 ], gender [ 174 176 , 178 180 ], extracerebral metastases [ 174 , 177 , 179 , 180 , 185 ], extracranial metastasis [ 178 ], number of metastases [ 177 , 178 , 185 ], the interval from first diagnosis to WBRT [ 174 , 177 , 179 ], KPS [ 178 , 185 ], primary tumor type [ 177 , 179 ] and RPA class [ 185 ] for treatment with WBRT alone.…”
Section: Resultscontrasting
confidence: 72%
“…18 Previously, we reported the early volumetric change, treatment outcome, and feasibility of low-dose WBRT plus local boost using 3-dimensional conformal radiotherapy (RT) for brain metastases. 19 However, the patients did not receive HS-WBRT, and boost RT was delivered after WBRT. The HS-WBRT with SIB using helical tomotherapy was adopted in our institution since 2011 and primary diagnosis of the majority of patients was adenocarcinoma of lung.…”
Section: Introductionmentioning
confidence: 99%